THE Staff Readiness to Change in Sungai Petani Community College Organization: a Pls-Sem Approach (International Journal of Scientific Research and Management (IJSRM), 2018)
Changes in the organization will take place when there is an objective change, direction and exchange of new management within an organization. The purpose of this study is to find the best approach to be used by the management in selecting the most contributing factors to stimulate the staff’s attitude for their readiness to change. Several contributing factors such as management and administration, organizational commitment and influence of peer group are seen as catalysts for staff readiness in Sungai Petani Community College (SPCC) to change. The research model was proposed with three hypotheses in responding the objective of the study. This quantitative study involves 74 respondents comprising staffs in the Sungai Petani Community College who are required to answer a set of questionnaires. This study uses descriptive statistical analysis using the SPSS version 21 software while the inferential statistics are used Partial Least Squares Structural Equation Modelling (PLS-SEM) version 3.0. The findings show that Influence of peer group factor has a positive impact on employee willingness in SPCC to change while management and administration factors as well as organizational commitment have a little significant effect on their willingness to change. The results of this study can help the management to use the stimulus factors that will help the organization in implementing the changes in the organization later. Keywords: Change Management, Management and Administration, Organizational Commitment, Influence of Peer Group, and Readiness to Change.